An Experimental Study on Botulinum Toxin Type A for the Treatment of Excessive Secretion after Submandibular Gland Transplantation in Rabbits - Shang Xie; Hui Xu; Bo Lin; Kan Wang; Xiao-Feng Shan; Zhi-Gang Cai (Journal of Ophthalmology)
Objectives. To investigate whether botulinum toxin type A (BTXA) could control excessive secretion after submandibular gland (SMG) transplantation in rabbits and its possible mechanisms. Methods. A new SMG transplantation model was established in rabbit. 30 successfully constructed models were randomly assigned to five groups including control group and four experimental groups. Secretion outputs were used to analyze the effect of BTXA injection on excessive secretion. Hematoxylin and eosin (HE) staining, transmission electron microscopy (TEM), Western blot, and immunofluorescence were performed to analyze its possible mechanisms. Results. After BTXA injection, a significant decrease of excessive secretion after SMG transplantation was found in 2 and 4 weeks groups, but no significant effect on 12 and 24 weeks groups. HE and TEM results showed that BTXA led to morphological and ultrastructural changes of acinar cells of transplanted SMG. Western blot results suggested that BTXA decreased the aquaporin-5 (AQP5) protein expression after BTXA injection for 2 and 4 weeks. Immunofluorescence results showed that AQP5 protein was mainly expressed in the cytoplasm after BTXA injection for 2 and 4 weeks, which might indicate that BTXA promoted AQP5 expression from the cell membrane to cytoplasm. Conclusion. BTXA could effectively control excessive secretion after SMG transplantation in rabbits.